0
$\begingroup$

Need help proving the following:

$\frac{dp}{d ln(t)} = t \frac {dp}{dt} $

This is what I have so far:

Applying chain rule.

$\frac{dp}{d ln(t)} = \frac {dp}{dt}\frac {dt}{d ln(t)} $

Simplifying:

$\frac {dp}{dt}\frac {dt}{d ln(t)} = \frac {dp}{dt}\frac {1}{\frac{d}{dt}} ln(t)$

Need assistance with the rest. Thanks!

$\endgroup$
  • $\begingroup$ $\frac {dt}{d \ln(t)}=\frac 1{\frac {d \ln(t)}{dt}}$ could help $\endgroup$ – Claude Leibovici Dec 10 '18 at 8:35
2
$\begingroup$

Leibniz's notations can sometimes be confusing. Writing something like $\frac{1}{\frac{\mathrm{d}}{\mathrm{d}t}}$ is terrible.

Let $p(t) = q(\ln(t))$. Then

$$\frac{\mathrm{d}p(t)}{\mathrm{d}\ln(t)} = \frac{\mathrm{d} q(\ln(t))}{\mathrm{d} \ln(t)} = q'(\ln(t)).$$ Here we treat $\ln(t)$ as a single variable.

Also,

$$\frac{\mathrm{d}p(t)}{\mathrm{d}t} = \frac{\mathrm{d}q(\ln(t))}{\mathrm{d}t}= q'(\ln(t))(\ln(t))'=q'(\ln(t))\frac{1}{t}.$$

$\endgroup$

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.